Legal Uncertainty as a Welfare Enhancing Screen - Matthias Lang (Center for Economic Studies and ifo Institute (CESifo), 2016)
Consider legal uncertainty as uncertainty about the legality of a specific action. In particular, suppose that the threshold of legality is uncertain. I show that this legal uncertainty raises welfare. Legal uncertainty changes deterrence in opposite directions. The probability of conviction increases for firms below the threshold, while the probability of conviction decreases for firms above the threshold. Hence, legal uncertainty acts as a welfare enhancing screen and increases welfare. Legal uncertainty discourages some actions with low private benefits, while it encourages other actions with high private benefits.
Keywords: D80; K20; K40; L50; 330; enforcement; deterrence; legal uncertainty; regulation; asymmetric information; incomplete contracts